Teacher and Family Working Together, the Case of a Father and his Autistic Son: An Action Research Experience - Rodríguez-Roblero, María del Rocío (Revista Electrónica Educare, 2015)
This paper describes the action research process experienced with a family over one year and shows the work done by the father, the teacher and an autistic child. The question proposed was: How do parents and the teacher work together to have a positive impact on the humanizing educational process of an autistic child? The paper presents the reflections emerging from this experience, as well as the uncertainty and anxiety of a teacher who does not know where to start working with the family. The action research model was the means to work and find spaces to jointly search for an answer. Playing was the instrument used to mediate in these spaces between the teacher, the parent and the child. The analysis of the observations shows that joint learning is brought about in each session. This research project evidenced the importance of family involvement in educational environments, not merely as recipients but as participants in the process.